Twenty‐year analysis of implant treatment in an Australian public dental clinic. (26th March 2018) - Duong, A; Dudley, J
Abstract: Background: This retrospective cohort study reviewed dental implant treatment completed at the Adelaide Dental Hospital over a 20‐year period. Methods: The database of implant treatment completed between 1996 and 2015 was analysed for patient, implant, prosthesis and operator specifics together with known implant status. Results: Three hundred and twenty patients (mean age, 51.50 years) were treated with 527 implants. One hundred and eighty‐four female patients received 296 implants and 136 males received 231 implants. Three hundred implants were restored with single crowns, 147 implants were restored with 63 mandibular implant overdentures, five implants were restored with two maxillary implant overdentures and 67 implants were restored with 20 full‐arch fixed prostheses. The overall known implant survival rate was 87.67%. Mandibular implant overdentures had a risk of implant failure four times that of single implant‐retained crowns that was statistically significant ( P = 0.0100). Conclusions: Implant treatment completed in this public sector clinic using finite resources and a defined system of patient and restorative selection criteria demonstrated a high known implant survival rate. Utilizing a structured and maintained patient recall protocol, it would be ideal to investigate further parameters of interest, particularly those that could improve treatment delivery and longevity.